Effect of Wood Saw Dust and Chopped Jute Fiber on the Tensile Properties of Epoxy Based Polymer Composite (Chemical Engineering Research Bulletin, 2021)
Polymer composites play a good role in various engineering applications because of their good combination of various properties such as unbeatable light weight, relatively high strength, ease of fabrication, corrosion resistance, high impact strength, design flexibility, dimensional stability, non-conductive properties, etc. So, polymer composites have attracted big attention from world-wide researchers. Epoxy based composite are largely used in load bearing application such as aerospace and automobile industries due to their good mechanical properties and corrosion resistance. In this research work, epoxy-based composites were developed by adding 5% wood saw dusts or 2 mm size chopped jute fibers. The jute fibers and saw dusts were added to gain some special property such as biodegradability. The developed composites were then characterized by tensile tests. Experimental results revealed that 5% saw dusts additions have no significant effect on the tensile strength of epoxy-based polymer composites. However, chopped jute fibers have been found to decrease the strength as well as fracture morphology noticeably.Chemical Engineering Research Bulletin 21(2020) 94-98